Testing Rural Early Educators Attitudes toward Children's Outdoor Recreation in Nature and Science: a new framework for exploring early educators' situated science teaching - Pedonti, Sarah; Becker, Derek R.; Watson, Myra K.; Grist, Cathy Lauren (Frontiers in Education, 2025)
IntroductionEarly childhood educators' dispositions toward science learning in outdoor environments play a critical role in fostering young children's engagement with science. However, existing tools do not sufficiently capture the values, beliefs, and experiences that shape these dispositions, especially in rural contexts. This study introduces a new framework and development of associated tool-the Testing Rural Early Educators' Attitudes toward Children's Outdoor Recreation in Nature and Science (TREE-ACORNS)-to assess early educators' perspectives on outdoor science learning.MethodsA sample of 108 early childhood educators, 66% of whom identified as residing in rural areas, completed the TREE-ACORNS survey. Preliminary validation of the TREE-ACORNS constructs was conducted using a structural equation modeling (SEM) framework to explore the relationships among constructs related to values for outdoor recreation, science teaching beliefs and costs, and science-related practices.ResultsFindings provide preliminary evidence that teachers' expectations and values around children's outdoor recreation are associated with their perceived science teaching costs, which in turn are indirectly related to their science beliefs, instructional practices, and support for outdoor learning. Additionally, rural-residing teachers reported lower perceived costs for science instruction and higher engagement in outdoor activities, indicating potential contextual strengths in rural early education settings.DiscussionThese results suggest that outdoor recreation and experiences may serve as effective entry points for promoting early science learning. The lower science-related costs reported by rural educators highlight a promising opportunity to leverage existing attitudes and experiences in rural communities to support high-quality science education in early childhood.